Cooperative and fully reversible color switching activation in hybrid graphene decorated nanocages and copper-TiO2 nanoparticles. (September 2020) - Tobaldi, D.M.; Lajaunie, L.; Dvoranová, D.; Brezová, V.; Figueiredo, B.; Seabra, M.P.; Calvino, J.J.; Labrincha, J.A.
Abstract: Nanostructured systems showing reversible color switching are envisaged to play a significant role in photo-switches, photo-optical sensors, smart windows, displays, optical storage memories. Most of the materials exhibiting reversible color switching are organic molecules. However, their UV-light activation, low thermal and chemical stability, as well as harmful synthesis methods, limit their extensive use. In this research, we have created an inorganic switchable photochromic material exploiting TiO2 ability of creating an exciton upon excitation, copper as the chromophore, and graphene's extraordinarily high electron mobility. Spatially-resolved electron energy-loss spectroscopy and aberration-corrected transmission electron microscopy imaging highlight the high sp 2 content of the graphene flakes as well as the presence of few-layers nanocage graphene decorating the surface of the flakes. Our material showed itself to be able to work under visible-light, its photochromic property being three times faster than conventional titania based photochromic materials, reaching a stable change in coloration after only 30 min of visible-light irradiation (vs. > 120 min in conventional Cu–TiO2 ). With the addition of just 1 wt% graphene, the material exhibited a staggeringly stable photochromic switching over repeated cycles. These results relate to the best previously reported values for any form of TiO2 -based photochromic material. This is therefore an excellent candidate for smart-windows, light-sensitive information and energy storage devices, and other chromic devices and applications. Graphical abstract: Image 1 Highlights: Inorganic photocatalytic color switching material & graphene decorated-nanocages. Purely visible-light induced photocatalytic color switching. Synergetic color switching activated by IFCT & photocatalysis. Fully reversible induced change in color over repeated switching cycles. Graphene to increase: (i) electric transport; (ii) thermal conductivity.